IMPROVING STUDENTS' SPEAKING ABILITY BY USING STORY TELLING (A CLASSROOM ACTION RESEARCH AT THE SECOND YEAR OF SMP NEGERI 2 GROGOL IN 2010/2011 ACADEMIC YEAR) - WULANDARI, RATNA (2011)
This research is aimed at describing the implementation of story telling and the result of improving students' speaking ability at the second year of SMPN 2 Grogol in 2010/2011 academic year. The subject of the study is limited to the second year students of SMPN 2 Grogol, consisting of 34 students. In this research, the writer carries out an action research. The action procedures are planning, implementing, observing, and reflecting. In the classroom action research, the writer uses test, observation, interview, and document to collect the data. The writer collects the data by giving pre-test before cycle then implementing the action research for two cycles. In the third meeting, she gives post test 1 in cycle 1 then post test 2 in cycle 2. In analyzing the data, the writer describes the implementation of story telling and she compares the result of pre-test and post-test before and after conducting the action research. The result of the action shows that the improving students' speaking ability by using story telling was successful. The writer concludes that improving students' speaking ability by using story telling is effective for the second year of SMPN 2 Grogol. The highest score of pre-test is 57, the lowest score is 32 and the mean score is 44, while highest score of post-test 1 is 73, the lowest score is 50 and the mean is 59 and also the highest score of post-test 2 is 86 , the lowest score is 65, the mean score is 72. Thus, the result of the research shows that storytelling can improve students' speaking ability in order to become appropriate technique in improving students' speaking ability. Practically, storytelling is the appropriate technique to improve students' speaking ability in order to be active learners. It is indicated that students learn best when they are personally involved in the teaching learning process. Improving speaking ability by using storytelling not only makes the students create their own stories, express idea, thinkcreatively, but also makes the students able to share ideas, information, or opinion to the other friends based on the story. It also provides an opportunity to develop accuracy, fluency, and keep the learners highly motivated.